Power‐ and polarization dependence of two photon luminescence of single CdSe nanowires with tightly focused cylindrical vector beams of ultrashort laser pulses. Issue 5 (4th August 2016) - Wang, Xiao; Zhuang, Xiujuan; Wackenhut, Frank; Li, Yunyun; Pan, Anlian; Meixner, Alfred J.
Abstract : We investigate two‐photon luminescence of single CdSe nanowires with high spatial resolution excited with tightly focused radially or azimuthally polarized laser beams allowing us to precisely control the excitation polarization in three dimensions. The nonlinear luminescence originates from the recombination of free carriers and exhibits a fourth order excitation power dependence for a two‐photon excitation process which can be perfectly modelled by rate equations. Abstract: We investigate two‐photon luminescence (TPL) of single CdSe nanowires (NWs) excited by tightly focused cylindrical vector beams of 150 fs pulses, achieving an optical resolution better than λ/4. Comparing the TPL images recorded by scanning the nanowires through the focal fields created either by a radially or an azimuthally polarized vector beam we observe a distinct anisotropic excitation efficiency which depends on the orientation of the electric field component with respect to the nanowire. The excitation anisotropy of the linear photoluminescence (PL) and TPL can directly be derived from the respective image patterns. Our results show that the highest TPL signal from a single NW is detected when the electric excitation field is parallel to the long axis of the NW, i.e. about one order of magnitude stronger than that excited along the short axis. We attribute the TPL to an emission mechanism based on the recombination of free carriers, which exhibits a fourth order excitation power dependence in low power regime and a second order power dependence in high power regime.